The story of America's birthday - Pingry, Patricia; Venturi-Pickett, Stacy, 1963- (Nashville, Tenn. : Candy Cane Press, 2000)
A simple board book that teaches children how America became free on July 4, 1776.
On board pages.
2.0
K-3
K-3
Keywords: Fourth of July -- Juvenile literature; United States. -- Juvenile literature; United States -- History -- Revolution, 1775-1783 -- Juvenile literature; Fourth of July; Holidays; United States; United States -- History -- Revolution, 1775-1783.; Fourth of July; Holidays; United States; United States -- History -- 1775-1783, Revolution